On Hadamard composition of Gelfond-Leont’ev derivatives of entire and analytic functions in the unit disk - Mulyava, Oksana; Sheremeta, Miroslav (My University, 2021)
For an entire function and an analytic in the unit disk function the growth of the Hadamard composition of their Gelfond-Leont'ev derivatives is investigated in terms of generalized orders. A relationship between the behaviors of the maximal terms of Hadamard composition of Gelfond-Leont'ev derivatives and of the Gelfond-Leont'ev derivative of Hadamard composition is established.
Keywords: analytical functions; Hadamard composition; Gelfond-Leont'ev derivative; maximal term; аналітичні функції; максимальний член; кафедра вищої математики імені проф. Можара В. І.